Intraneural Ganglion in Superficial Radial Nerve Mimics de Quervain Tenosynovitis - Haller, Justin M.; Potter, Michael Q.; Sinclair, Micah; Hutchinson, Douglas T. (Journal of Wrist Surgery, 2014)
Background Intraneural ganglions in peripheral nerves of the upper extremity are extremely rare and poorly understood.Case Description We report a patient with symptoms consistent with de Quervain tenosynovitis who was found to have an intraneural ganglion in the superficial radial nerve. The ganglion did not communicate with the wrist joint. We removed the intraneural ganglion, and the patient's symptoms resolved. At her 6-month postoperative follow-up, she remained asymptomatic.Literature Review: There is only one case report of intraneural ganglion in the superficial radial nerve. In that case, the patient had symptoms consistent with nerve irritation, including radiating pain and paresthesias. In contrast to that previous report, the patient in the current case had only localized pain, no paresthesias, and a physical exam consistent with de Quervain tenosynovitis.Clinical Relevance This case demonstrates that an intraneural ganglion cyst can mimic the symptoms of de Quervain tenosynovitis without the more usual presentation of painful paresthesias.
Keywords: tenosynovitis; ganglion cyst